2022
DOI: 10.1111/ipd.12955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fit accuracy between conventional and CAD/CAM‐fabricated band–loop space maintainers

Abstract: Aim:The aim of this in vitro study was to evaluate the band fit of metallic bandloop space maintainers fabricated by conventional and 3D printing technologies for clinical applications.Design: Sixteen digital intraoral impressions were selected, and resin models were printed with a 3D printer. Forty band-loop space maintainers were fabricated (20 each for both the conventional and digital groups). To evaluate the band fit of conventional and CAD/CAM-fabricated space maintainers, cement space was visualized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…3D design and manufacturing have lessened the time-lasting process of manufacturing prosthetic restorations, removable and fixed orthodontic devices, space maintainers, dental crowns, and surgical guides. [21][22][23][24][25] is design also has the advantage of personal customizing following the needs of individuals. e single-unit manufacturing of the appliance removes the risk of solder breakage and eliminates the laboratory process, lessening the chairside time by simplifying the complex workflows.…”
Section: Discussionmentioning
confidence: 99%
“…3D design and manufacturing have lessened the time-lasting process of manufacturing prosthetic restorations, removable and fixed orthodontic devices, space maintainers, dental crowns, and surgical guides. [21][22][23][24][25] is design also has the advantage of personal customizing following the needs of individuals. e single-unit manufacturing of the appliance removes the risk of solder breakage and eliminates the laboratory process, lessening the chairside time by simplifying the complex workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical resistance, high-temperature stability, dimensional stability and a wide range of processing possibilities are all provided by the material. There are some studies of posterior fixed maintainers [33][34][35][36] that showed satisfaction in the young patients. However, there has been no study about aesthetic space maintainers with this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…After performing a best-fit alignment, the abutment teeth were selected, and a 3D deviation analysis was conducted. The results indicated no significant differences in the fit of the conventional and 3D-printed metallic band-loop space maintainers (p-value = 0.56) [39].…”
mentioning
confidence: 86%